Studium ekonomiczne polskiego systemu emerytalnego - Mikołajek, Martyna (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
One of the fundamental functions of the pension system is to protect the insured from deprivation as they approach the retirement age. This is coupled with the maintenance of a stable system that is able to provide beneficiaries with benefits until the end of their lives. Since the pension system is strongly dependent on the demographic and economic situations in a given country, it is important that policy in this matter is conducted prudently. The purpose of the article was to describe and analyze the Polish pension system with the reforms implemented during the last two decades. The additional purpose was also to present general definitions related to the concept of the pension system and the essence of the pension security operation.
Keywords: pension systems; Open Pension Funds; Social Security Institution; Social Insurance Fund; demography; social insurance